3(x + 3 ) - 1 = 2
pfvr :(
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
3(x+3) - 1 =2
3x + 9 - 1 = 2
3x = 2 - 9 + 1
3x = -7 + 1
3x = -6
x = -6/3
x = -2
mineirof392:
obgd
Respondido por
1
Resposta:
x = -2
Explicação passo-a-passo:
3 (x + 3) - 1 = 2
3x + 9 - 1 = 2
3x + 8 = 2
3x = 2 - 8
3x = -6
x = -6/3
x = -2
3 (2 + 3) - 1 = 2
3.1 - 1 = 2
3 - 1 = 2
Perguntas interessantes
Matemática,
8 meses atrás
Química,
8 meses atrás
Espanhol,
9 meses atrás
Português,
9 meses atrás
Matemática,
1 ano atrás